2021
DOI: 10.1108/rpj-07-2020-0181
|View full text |Cite
|
Sign up to set email alerts
|

Designing and simulating a “mass selective customization-centralized manufacturing” business model for clothing enterprises using 3D printing

Abstract: Purpose Global economic growth provides new opportunities for the development of clothing enterprises, but at the same time, the rapid growth of clothing customization demand and the gradual increase of clothing costs also pose new challenges for the development of clothing enterprises. In this context, 3D printing technology is injecting new vitality and providing a new development direction for the vigorous development of clothing enterprises. However, with the application of 3D printing technology, more and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Few studies focused on both the design of CBMC and their dynamic analysis (e.g., Cosenz and Bivona., 2021;Jin et al, 2021;Feng et al, 2021;Zapata Riveros et al, 2021) and just one study (Melkonyan et al, 2017) focused on designing an SBMC as well as analyzing it dynamically.…”
Section: Design and Dynamic Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies focused on both the design of CBMC and their dynamic analysis (e.g., Cosenz and Bivona., 2021;Jin et al, 2021;Feng et al, 2021;Zapata Riveros et al, 2021) and just one study (Melkonyan et al, 2017) focused on designing an SBMC as well as analyzing it dynamically.…”
Section: Design and Dynamic Analysismentioning
confidence: 99%
“…Although the SD approach has been widely used in business models (Cosenz and Bivona, 2021;Jin et al, 2021) and sustainable business models (Melkonyan et al, 2017;Täuscher and Abdelkafi, 2018), there has not been found a comprehensive methodology to design SBMs and analyze the dynamics of the designed models so as to identify the policies for possible future scenarios.…”
Section: System Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The core of 3D printing technology is to find suitable materials by establishing a digital model, and computer printing work through the digital model, and finally complete the product manufacturing. The development of technology in modern society makes the thinking of designers in the field of apparel design no longer present a single characteristic, and we can use technical means to change the traditional mode of apparel design [1]. Starting from the model, parts, or application of the depth of interpretation of the relationship between 3D printing and apparel design and the future development of a comprehensive judgment.…”
Section: Introductionmentioning
confidence: 99%